Four‐dimensional flow assessment of pulmonary artery flow and wall shear stress in adult pulmonary arterial hypertension: Results from two institutions. Issue 5 (27th June 2014) - Barker, Alex J.; Roldán‐Alzate, Alejandro; Entezari, Pegah; Shah, Sanjiv J.; Chesler, Naomi C.; Wieben, Oliver; Markl, Michael; François, Christopher J.
Abstract : Purpose: To compare pulmonary artery flow using Cartesian and radially sampled four‐dimensional flow‐sensitive (4D flow) MRI at two institutions. Methods: Nineteen healthy subjects and 17 pulmonary arterial hypertension (PAH) subjects underwent a Cartesian 4D flow acquisition (institution 1) or a three‐dimensional radial acquisition (institution 2). The diameter, peak systolic velocity (Vmax), peak flow (Qmax), stroke volume (SV), and wall shear stress (WSS) were computed in two‐dimensional analysis planes at the main, right, and left pulmonary artery. Interobserver variability, interinstitutional differences, flow continuity, and the hemodynamic measurements in healthy and PAH subjects were assessed. Results: Vmax, Qmax, SV, and WSS at all locations were significantly lower ( P < 0.05) in PAH compared with healthy subjects. The limits of agreement were 0.16 m/s, 2.4 L/min, 10 mL, and 0.31 N/m 2 for Vmax, Qmax, SV, and WSS, respectively. Differences between Qmax and SV using Cartesian and radial sequences were not significant. Plane placement and acquisition exhibited isolated, site‐based differences between Vmax and WSS. Conclusions: 4D flow MRI was used to detect differences in pulmonary artery hemodynamics for PAH subjects. Flow and WSS in healthy and PAH subject cohorts were similar between Cartesian‐ and radial‐based 4D flow MRI acquisitions with minimal interobserver variability. Magn Reson Med 73:1904–1913, 2015. © 2014 Wiley Periodicals, Inc.